FAKTOR-FAKTOR YANG MEMENGARUHI HASIL TANGKAPAN IKAN DENGAN ALAT TANGKAP PUKAT CINCIN DI DESA PARANGGI KECAMATAN AMPIBABO KABUPATEN PARIGI MOUTONG - Mengkopi, Firdaus; Laapo, Alimudin; Br. Manurung, Dewi Sartika l. (Fakultas Pertanian, Universitas Tadulako, 2023)
The purpose of this study is to assess the effect of operational costs, length of time at sea, ship engine, distance covered at sea, and experience at sea on the catches of purse seine fisherman in Paranggi Village, Ampibabo Sub District, Parigi Moutong District from November 2020 to January 2021. According to the study's findings, operational costs, duration of sea trips, ship engine, distance travelled at sea, and experience at sea all influence the capture of fish with purse seiners in Paranggi Village, Ampibabo District, Parigi Moutong Regency.